Réponse :
salut
1) développement
(x+2)(4x-1)-(x-5)(x+2) => forme 1
4x²-x+8x-2-(x²+2x-5x-10)
4x²-x+8x-2-x²-2x+5x+10
3x²+10x+8 => forme 2
factorisation
(x+2)(4x-1-x+5)
(x+2)(3x+4) => forme 3
2) f(0) forme 2
3*0²+10*0+8= 8
f(-2) forme 3
(-2+2)(3x+4)
0(3x+4)= 0
f(racine(3)) forme 2
3*(racine(3))²+10*racine(3)+8
=9+10*racine(3)+8
= 17+10*racine(3)
f(1/3) forme 3
((1/3)+2)(3*(1/3)+4) = 35/3
3) f(x)=8 forme 2
3x²+10x+8=8
3x²+10x=0
on factorise
x(3x+10)
x=0 et x= -10/3
4) f(x)=0 forme 3
(x+2)(3x+4)
x+2=0 => x=-2
3x+4=0 => x= -4/3
Explications étape par étape